PENGARUH FAKTOR EKONOMI, SOSIAL DAN DEMOGRAFI TERHADAP KEPUTUSAN IBU RUMAH TANGGA UNTUK BEKERJA PADA USAHA PEMBUATAN BANTEN DI KOTA DENPASAR - Dwi Saputra Ida Bagus; Marhaeni A.A.I.N. (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2018)
Work on the business of making offerings began ogled by most housewives (IRT) in Denpasar because the work will be necessary Banten maker semasih Hinduism in Bali carrying out religious ceremonies. The aim of this study are: 1) analyze the influence simultaneously and partially age, income, husband's income, number of dependents, and ease of doing the work of the IRT's decision to work on the business of making offerings in Denpasar; 2) determine the sequence of the probability of each independent variable; 3) know is there any difference between the income of housewives who work and do not work in the business of making offerings. This study uses primary data analysis method Binary Logistic. Reslults of this study shown us that all independent variables simultaneously and significant influence on the decision IRT to work on making business offerings. Age, income, and number of dependents, positive and significant effect partially to the decision IRT to work on the business of making offerings, ease of doing significant effect on the decision IRT to work on the business of making offerings while revenues husband did not significantly influence the IRT's work on making business offerings. Variable ease of doing the work have the highest probability value, followed by a variable income, number of dependents, age and income of the husband. In addition, there is a difference between income IRT is working and not working in the business of making offerings in Denpasar. Keywords: Decisions, Housewife (IRT), Banten, Work.